Induced Resistance for Plant Defence - Andres A. Borges (Frontiers Research Topics, 2016)
In this century the human being must face the challenges of producing enough to feed a growing population in a sustainable and environmentally friendly way. The yields are with increasing frequency affected by abiotic stresses such as salinity, drought, and high temperature or by new diseases and plagues. The Research Topic on Induced Resistance for Plant Defense focuses on the understanding the mechanisms underlying plant resistance or tolerance since these will help us to develop fruitful new agricultural strategies for a sustainable crop protection. This topic and its potential applications provide a new sustainable approach to crop protection. This technology currently can offer promising molecules capable to provide new long lasting treatments for crop protection against biotic or abiotic stresses. The aim of this Research Topic is to review and discuss current knowledge of the mechanisms regulating plant induced resistance and how from our better understanding of these mechanisms we can find molecules capable of inducing this defence response in the plant, thereby contributing to sustainable agriculture we need for the next challenges of the XXI century.